Case study of housing unit customization in a multifamily residential real estate development in the City of Fortaleza, State of Ceará, Brasil (Research, Society and Development, 2024)
Faced with a highly competitive market, the construction industry adopted the strategy of offering project customization services to meet the demands of a more discerning clientele seeking unique products. Clients have the opportunity to personalize, adapt, and adjust the project according to their individual needs. These projects can offer flexibility by allowing various spatial configurations, diverse uses, and expansions, but they can also be adapted from a single initial design, with the possibility of making changes during the sales and construction phases. However, such modifications can present challenges and setbacks for the construction company, requiring the implementation of effective process control, including transparent communication both with clients and between the different sectors involved in the production process. The objective of this study was to review the process and propose an update in the way the company interacts with clients and operates, as well as for other companies in the same real estate and construction segment. The methodology used was a Case Study, carried out in a Development and Construction company in the city of Fortaleza, Ceará – Brazil, through documentary research, data collection from the company, and the gathering of project modifications submitted by clients. Furthermore, it was necessary to understand the procedures adopted by the company to accommodate project changes requested by buyers.